2008
DOI: 10.1007/s00420-008-0336-y
|View full text |Cite
|
Sign up to set email alerts
|

Parameters influencing health variables in a sample of 949 German teachers

Abstract: Our data demonstrate that interpersonal factors appear to play a prominent role with respect to both strain and protection of teachers' health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 12 publications
(32 reference statements)
4
37
0
5
Order By: Relevance
“…Our findings are consistent with several previous studies that are based on teachers' self-perceptions of pupil problem behaviour and teachers' stress and burnout (Bauer et al, 2006;Bauer et al, 2007;Borg et al, 1991;Geving, 2007;Hastings & Bham, 2003;Kovess-Masféty et al, 2007;Kyriacou & Sutcliffe, 1978;Moreno-Abril et al, 2007;O'Connor & Clarke, 1990;Unterbrink et al, 2008). Perceived pupils' problem behaviour is consistently associated with teachers' stress and burnout in these studies.…”
Section: Tablesupporting
confidence: 95%
See 1 more Smart Citation
“…Our findings are consistent with several previous studies that are based on teachers' self-perceptions of pupil problem behaviour and teachers' stress and burnout (Bauer et al, 2006;Bauer et al, 2007;Borg et al, 1991;Geving, 2007;Hastings & Bham, 2003;Kovess-Masféty et al, 2007;Kyriacou & Sutcliffe, 1978;Moreno-Abril et al, 2007;O'Connor & Clarke, 1990;Unterbrink et al, 2008). Perceived pupils' problem behaviour is consistently associated with teachers' stress and burnout in these studies.…”
Section: Tablesupporting
confidence: 95%
“…These behaviours are linked to a number of factors related to pupils' home, friends, school, and health (Luopa, Pietikäinen, & Jokela, 2006, and international comparisons 1978; Moreno-Abril et al, 2007;O'Connor & Clarke, 1990;Unterbrink et al, 2008). However, the vast majority of these studies has relied solely on teachers' self-reports, introducing a potential common method bias arising from response styles and the fact that psychological distress may affect the perceptions of environmental factors, such as the workplace itself.…”
Section: Introductionmentioning
confidence: 97%
“…Various studies, including some of our own, have shown that coping with interpersonal problems in school is among the primary factors inXuencing teachers' health. This holds true not only when teachers are asked to rate which factors contribute most to their job strain (Bauer et al 2006) but also when diVerent factors are statistically analyzed regarding their impact on teachers' health: we were able to show that positive feedback by parents and pupils or support from colleagues and school heads had a signiWcant, pre-emptive inXuence on teachers' health (Unterbrink et al 2008). In fact, it is apparent that teachers are exposed to high rates of hostile encounters, entailing verbal aggression, threats of violence, as well as actual experiences of violence (Bauer et al 2007).…”
Section: Introductionmentioning
confidence: 71%
“…A number of studies have highlighted the importance of structural and organizational adjustments to improve and simplify the work situation of teachers [5,7,8]. A supportive leadership style by senior management using effective communication, formulating feasible targets, and creating a positive atmosphere among colleagues and in the classroom can prevent stress among teachers and students.…”
Section: Discussionmentioning
confidence: 99%